2009
DOI: 10.1007/s00127-009-0062-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mental well-being in medical students

Abstract: Psychological distress was significantly greater in our sample of Hungarian medical students than in the same age group of the general population. Psychological distress is strongly related to SOC and can be estimated by our proposed models. Both SOC and psychological distress can be used to characterize the mental health of future medical doctors, the improvement of which needs attention even during their training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 27 publications
5
46
0
9
Order By: Relevance
“…Male undergraduates showed better mental health status than females but the difference was not statistically significant. This finding was similar with the results of previous study done by Song, Huang, Liu, Kwan, Zhang, Sham & Tang (2008), Biro et al, (2009), Pavot, Fujita & Diener (1997, Zaid et al, (2007) and Sherina et al,. (2003).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Male undergraduates showed better mental health status than females but the difference was not statistically significant. This finding was similar with the results of previous study done by Song, Huang, Liu, Kwan, Zhang, Sham & Tang (2008), Biro et al, (2009), Pavot, Fujita & Diener (1997, Zaid et al, (2007) and Sherina et al,. (2003).…”
Section: Discussionsupporting
confidence: 83%
“…However, a review of literature on the subject reveals that information regarding mental health among undergraduates were derived from studies done outside Malaysia (McKinney, 2005;Sreeramareddy, Shankar, Binu, Mukhopadhyay, Ray & Menezes, 2007;Hamdan-Mansour et al, 2009;Uner, Ozcebe, Telatar & Tezcan, 2008;Abdulghani, 2008;Biro, Balajti, Adany & Kosa, 2009). In Malaysia, research on mental health was more focused on medical students rather than on the general students population.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was similar to that used in previous surveys among medical [17], public health [18], and preschool teacher students [19], and included scales on perceived health, mental health, demographic (age, sex, residence) and socioeconomic (parents' educational level, family's economic status) data. Items not referred separately were taken from the tool of the Hungarian National Health Interview Survey of 2003 [20].…”
Section: Data Collectionmentioning
confidence: 99%
“…In recent years, there has been an increased interest in mental health problems among medical students (1)(2)(3)(4). Depression and anxiety are the most common problems, and previous studies have reported a higher prevalence of depression and anxiety symptoms among medical students in comparison to the general population (1,3) and in comparison to other peers not in medical education (5).…”
Section: Introductionmentioning
confidence: 99%